An examination of certain counterpart accounts - Milford, J (2022)
This work is closely tied to the metaphysical and formal work of David Lewis on modality. First, to Lewis’ reduction of modality in terms of his modal realism and mature counterpart machinery. Second, to Lewis’ 1968 formal account (and its subsequent developments) employing a notion of counterparthood, an account that is detachable from Lewis’ full-blooded metaphysics. This work is primarily an examination of both of these accounts, as well as five other formal accounts that, inspired by Lewis’ work, employ a notion of counterparthood.